Effect of debt, profit, company size and cash flow on financial distress in financial institution companies - Hartono Rukmana; Mila Yulia Herosian; Erlangga Jody Fanggano; Calvin Wijaya (Enrichment : Journal of Management, 2023)
The purpose of this is to test and analyze how debt, profit, company size, and cash flow affect financial distress in financing companies on the IDX for the 2016-2020 period, either partially or simultaneously. This research includes quantitative descriptive research. The population of this study was 16 financial institution companies on the Indonesia Stock Exchange and the sample used a purposive sampling technique to obtain data from 9 companies with a total of 45 observations. The statistical method is multiple linear regression analysis. The results of the research show that the classical assumptions have met the requirements. Partially (t-test), Debt, Profit, Company Size, and Cash Flow have a significant effect on Financial Distress. Simultaneously (test F) Debt, Profit, Firm Size, and Cash Flow have a significant effect on Financial Distress. The magnitude of the coefficient of determination is 97.8% while the remaining 2.2% of Financial Distress is explained by other variables not examined in this study.